Effects of Percutaneous LVAD Support on Right Ventricular Load and Adaptation - Yourshaw, Jeffrey P.; Mishra, Prabodh; Armstrong, M. Christopher; Ramu, Bhavadharini; Craig, Michael L.; Van Bakel, Adrian B.; Steinberg, Daniel H.; DiSalvo, Thomas G.; Tedford, Ryan J.; Houston, Brian A. (Journal of cardiovascular translational research, 2019)
Both operative and hemodynamic mechanisms have been implicated in right heart failure (RHF) following surgical left ventricular assist device (LVAD) implantation. We investigated the effects of percutaneous LVAD (pLVAD; Impella®, Abiomed) support on right ventricular (RV) load and adaptation. We reviewed all patients receiving a pLVAD for cardiogenic shock at our institution between July 2014 and April 2017, including only those with pre- and post-pLVAD invasive hemodynamic measurements. Hemodynamic data was recorded immediately prior to pLVAD implantation and up to 96 h post-implantation. Twenty-five patients were included. Cardiac output increased progressively during pLVAD support. PAWP improved early post-pLVAD but did not further improve during continued support. Markers of RV adaptation (right ventricular stroke work index, right atrial pressure (RAP), and RAP to pulmonary artery wedge pressure ratio (RAP:PAWP)) were unchanged acutely implant but progressively improved during continued pLVAD support. Total RV load (pulmonary effective arterial elastance; E A ) and resistive RV load (pulmonary vascular resistance; PVR) both declined progressively. The relationship between RV load and RV adaptation (E A /RAP and E A /RAP:PAWP) was constant throughout. Median vasoactive-inotrope score declined after pLVAD placement and continued to decline throughout support. Percutaneous LVAD support in patients with cardiogenic shock did not acutely worsen RV adaptation, in contrast to previously described hemodynamic effects of surgically implanted durable LVADs. Further, RV load progressively declined during support, and the noted RV adaptation improvement was load-dependent as depicted by constant E A /RA and E A /RAP:PAWP relationships. These findings further implicate the operative changes associated with surgical LVAD implantation in early RHF following durable LVAD.